2008
DOI: 10.1029/2007wr006478
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐dependent desorption of uranium from contaminated subsurface sediments

Abstract: [1] Column experiments were performed to investigate the scale-dependent desorption of uranyl [U(VI)] from a contaminated sediment collected from the Hanford 300 Area at the U.S. Department of Energy (DOE) Hanford Site, Washington. The sediment was a coarse-textured alluvial flood deposit containing significant mass percentage of river cobble. U(VI) was, however, only associated with its minor fine-grained (<2 mm) mass fraction. U(VI) desorption was investigated both from the field-textured sediment using a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
292
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 135 publications
(309 citation statements)
references
References 33 publications
13
292
0
Order By: Relevance
“…A four-fold increase in alkalinity resulted in a 2.5-fold increase in the initial rate of release of U(VI) after each of the stop flow events. This is in good agreement with the 2.2-fold increase predicted by the multi-rate SCM model (Liu et al, 2008;Yin et al, 2008). Approximately 80% of the labile U(VI) was extracted with AGW containing 1 meq/L alkalinity and ~95% using an AGW with 4 meq/L (Figure V-3).…”
Section: Grain-scale U(vi) Desorption Rate Experimentssupporting
confidence: 80%
See 3 more Smart Citations
“…A four-fold increase in alkalinity resulted in a 2.5-fold increase in the initial rate of release of U(VI) after each of the stop flow events. This is in good agreement with the 2.2-fold increase predicted by the multi-rate SCM model (Liu et al, 2008;Yin et al, 2008). Approximately 80% of the labile U(VI) was extracted with AGW containing 1 meq/L alkalinity and ~95% using an AGW with 4 meq/L (Figure V-3).…”
Section: Grain-scale U(vi) Desorption Rate Experimentssupporting
confidence: 80%
“…Over the following pore volumes, changes in major ion concentrations steadily approached those expected based on changes in the influent concentrations. Trends in U(VI) desorption in column #1 were similar to those reported previously for vadose-zone U(VI)-contaminated sediments from the site (e.g., Qafoku et al, 2005;Liu et al, 2008), with an initial rapid decline in U(VI) followed by a long tail ( Figure V-7a). Trends in U(VI) desorption in column #2 were generally consistent with imposed water composition changes ( Figure V-7b).…”
Section: Effects Of Variable Groundwater Composition and Water Table supporting
confidence: 73%
See 2 more Smart Citations
“…This experimental approach, however, has the potential disadvantages of preferential flow paths, transport-limited rather than surface-limited reactions, and non-uniform contact of the reactant solution with surfaces (Steefel and Maher, 2009;Zhu, 2009). Column experiments have been used to study the release of U from contaminated soils and sediments under different environmental conditions (Qafoku et al, 2005;Liu et al, 2008;Eagling et al, 2013). However, no studies have reported dissolution rates of uranyl oxyhydroxide minerals under thermodynamically undersaturated and/or dynamic conditions of flow within porous media to simulate subsurface conditions.…”
Section: Introductionmentioning
confidence: 99%